The perspective of historical sociology : the indiviual as homo-sociologicus through society and history - Šubrt, Jiří, 1958- (Emerald Publishing Limited, 2017)
This book provides a comprehensive overview of the range of themes which make up the field of Historical Sociology. Jiří Šubrt systematically discusses the main problems of societal development, long term process and changes in the key areas of social life. These include not only temporalized sociology, evolutionary theory, civilizational analysis, societal systems, structures and functions, but also modernization and revolution, risk, crisis, catastrophe and collapse, wars, conflicts and violence, nations, nationalism and collective memory. This study does not ignore the fundamental dichotomy underlying the discipline, which is between individualism and holism. At the heart of this book lies the human individual as related to social and historical development. The key question is who or what is responsible for the process of human history: society or the individual? The author concludes by offering an approach which may help in resolving this dilemma.